Improving Students’ Writing Skill by Applying Fishbone Techniques at the Grade X MAN 2 Padang Lawas - susi melyana harahap; Nazriani Lubis (Indonesian Journal of ELT and Applied Linguistics, 2023)
This study aims to determine the improvement achieved by students in the ability to write descriptive text using the fishbone technique. This research was conducted by applying quantitative research method and an experimental research design consisting of pre-test, treatment and post-test to improve students' descriptive writing skills using the fishbone technique in class X MAN 2 Padang Lawas. The instruments used are writing descriptive text materials based on a given topic, written test, fishbone improved by the students and lesson plan (RPP). To assess students' performance in writing descriptive text, several criteria are used. The cumulative score ranges from (0-100). To determine student achievement in writing there are several criteria that are considered to have five scales of assessment components namely content, organization, vocabulary, use of language, and mechanism. After analyzing the data, it is concluded that there is significant effectiveness of using the Fishbone Technique on the student's writing skill. The finding shows that the score of t (effect) is 0.06. Therefore the effect of using the Fishbone Technique has a significant effect on students' achievement in writing skills.